Comparing the Effectiveness of Written Emotional Disclosure Training and Cognitive-Behavioral Group Training on Internalizing and Externalizing Disorders of Students in Elementary School - Mohammad Raesi; Faride Sadat Hoseini; Yosof Dehghani (Iranian Evolutionary Educational Psychology Journal)
Objective: The purpose of this study is to determine the effectiveness of Written Emotional Disclosure Training and Cognitive-Behavioral Group Training on the internalizing and externalizing disorders of students in elementary school. Methods: This study presents a quasi-experimental design incorporating a pretest-post-test control group. A total of 45 participants were chosen from the second-grade elementary students using random sampling methods. The research utilized various instruments including The Difficulties in Emotion Regulation Scale (DERS), Kovacs’ Children's Depression Inventory (CDI), Shahim Relational and Explicit Aggression Scale, and The Conners’ Teacher Rating Scale (CTRS-R). The participants were divided into three equal groups of 15 individuals each, representing the first, second, and control groups. All participants underwent the initial pretest phase. Subsequently, the first group received 10 sessions of Cognitive-Behavioral Group Training, the second group received 4 sessions of Written Emotional Disclosure Training, while the control group did not receive any training. Following this, a post-test was conducted on all participants. The data obtained were analyzed using multivariate analysis of covariance (MANCOVA). Results: The results revealed a significant variance in the efficacy of Cognitive-Behavioral Group Training and Written Emotional Disclosure Training across the experimental and control groups during the post-test. This suggests that both interventions can effectively mitigate internalizing and externalizing issues among elementary school students. Furthermore, no significant difference emerged between those who underwent Cognitive-Behavioral Group Training and those who underwent Written Emotional Disclosure Training in terms of internalizing and externalizing problems, indicating similar levels of effectiveness. Conclusions: The study implies that both Cognitive-Behavioral Group Training and Written Emotional Disclosure Training are cost-effective, efficient, and compatible strategies for addressing internalizing and externalizing problems in individuals